Sustainable Work Ability and Aging - Clas-Håkan, Nygård (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In many industrialized countries, there is a sharp increase of the aging population due to a decrease in fertility rate and an increase in life expectancy. Due to which, the age dependency ratio rises and may cause increased economic burden among working age population. One strategy to combat this problem is to prolong peoples working career. A sufficient work ability is a requirement for a sustainable and prolonged employment. Work ability is primarily a question of balance between work and personal resources. Personal resources change with age, whereas work demands may not change parallel to that, or only change due to globalization or new technology. Work ability, on average, decreases with age, although several different work ability pathways exist during the life course. Work-related factors, as well as general lifestyle, may explain the declines and improvements in work ability during aging. A sustainable work ability throughout the life course is a main incentive for a prolonged working career and a healthy aging. Work ability and work-related factors, are therefore important occupational and public health issues when the age of the population increases. This Special Issue, "Sustainable Work Ability and Aging", includes in all 16 original articles and one opinion paper, organized in three sections. The research topics cover